Thermal Optimization Of Ice Cream Making Process : Comparison Between R134A And R404A Refrigerants - Azmi, Mohd Azreen (2019)
Refrigerant is a medium or working substance in a cooling and refrigeration system that run through all the inner parts of the refrigerator. The use of the right refrigerant in the system is important because it can help to shorten the ice cream processing time and increase the production capacity. The system optimization will help to ensure the system is working in an optimal condition with minimal energy loss. At the same time the selection of appropriate refrigerant can improve the efficiency of the refrigeration system, hence reduce the power consumption. The objectives of this project are to redesign and fabricate the ice-cream making machine as the test rig of this project and to identify which of the two refrigerants (R134a and R404a) is better in term of cooling rate for ice cream making process. The experiments to compare performance of those refrigerants were conducted using a test rig, design and built using standard refrigeration system components for ice cream machine. The data collected were time taken to reach the ice-cream freezing temperature ( -8° C) and temperature reading during the freezing process for every 10 minutes interval for one hour. The experiments were replicated three times. Performance of the two refrigerants was compared using t-test and paired t-test analysis utilizing Minitab software. The t-test results indicated that statistically refrigerant R404a reached the freezing time in shorter time compared to that of R134a. The paired t-test also indicated that the refrigerant R404a’s temperature readings during the freezing process is statistically lower than that of R134a’s.